The beliefs and practices of pre-service teachers and the relationship to theoretical orientation to reading: a case study - Broman, Sarah Elizabeth (Kansas State University, 2018)
All human beings possess within them implicit and explicit theories which they use repeatedly throughout their lives to explain a wide array of experiences (Tracey & Morrow, 2017). In education, teachers use their theories about reading and learning to read to inform nearly every aspect of their instruction. These belief systems develop over a lifetime and are used as filters when making instructional decisions (Cunningham & Fitzgerald, 1996; Prawat, 1992; Richardson, Anders, Tidwell, & Lloyd, 1991; Smith, 2004). Understanding and identifying these theoretical perspectives empowers educators to make informed instructional decisions in the classroom while also clarifying and defining their roles as teachers. While numerous studies have documented the relationship between teachers’ beliefs and instructional practices, there appeared to be limited research that related preservice teachers’ beliefs and practices to their personally held theoretical perspectives. This study explored pre-service teachers’ beliefs and practices and how they related to their theoretical orientations to reading. The study specifically addressed the gap in the research focusing on pre-service teachers who were enrolled in a literacy methods course. Multiple data sources were gathered from interviews, observations, and artifacts and documents. These data were collected and analyzed throughout the duration of the study. The study’s findings established the relationship between pre-service teachers’ theoretical orientations to reading and their beliefs and instructional practices. The data analysis revealed that the pre-service teachers’ previous life experiences, and experiences in the literacy methods course and corresponding internship influenced their theoretical orientations to reading. Further data analysis also revealed inconsistencies related to the alignment of pre-service teachers’ beliefs and instructional practices and change of theoretical orientations.
Keywords: Teacher education; Beliefs and practices; Theoretical orientation to reading; Reading educationPre-service teachers